Developing assessment literacy of future mathematics teachers: An integrative approach - I. B. Shmigirilova; A. S. Rvanova; A. A. Tadzhigitov; O. L. Kopnova (Russian State Vocational Pedagogical University, 2024)
Introduction. Assessment of student learning outcomes, properly carried out by a teacher, can be a powerful tool for improving the quality of school education. In this regard, the development of the assessment literacy of future teachers around the world is recognised as an important task of their university training. The urgency of solving this problem increases even more in connection with the transition of educational systems to criteria-based assessment.Aim. The present research aims to characterise the features of integrative approach to the formation of assessment literacy of a future teacher and present the experience of its implementation in the framework of the training of teachers of mathematics in a Kazakh university.Methodology and research methods. Comparative and aspect-based analysis of scientific and methodological literature on the development of teachers' assessment literacy became the basis for the theoretical stage of the study. 36 undergraduate students studying in the Mathematics programme were selected as participants in the experimental phase of the study. The collection of quantitative data on changes in student assessment literacy was carried out using the ACAI tool, which consists of three parts with closed questions concerning various aspects of teacher assessment approaches. Methods of mathematical statistics were used for data processing. The collection of additional qualitative data on what had the greatest impact on the development of the assessment literacy of future mathematics teachers was carried out on the basis of a focus group interview.Results and scientific novelty. In the process of theoretical analysis, the authors summarised the characteristics of assessment literacy as a significant component of a teacher's professional competence. Also, the authors identified five areas, whose implementation in the process of university training will contribute to the development of the readiness of future teachers to carry out competent professional assessment activities. The empirical data obtained confirmed that an integrative approach has a significant impact on the development of assessment literacy of future teachers as it combines: special assessment course; assignments and assessment practices in the study of mathematical, pedagogical and methodological university disciplines; personal experience in the implementation of assessment activities in the course of teaching practice at school; and the possibility of interacting with experienced acting teachers on educational assessment.Practical significance. The study contributes to the expansion of ideas about the features of assessment in university training teacher. In addition, the experience presented in the article can be used in determining the directions for improving the professional training of teachers in various contexts of subject areas.